(untitled) - Rachev, S. T (Hoboken, N.J., 2008)
This groundbreaking book extends traditional approaches of risk measurement and portfolio optimization by combining distributional models with risk or performance measures into one framework. Throughout these pages, the expert authors explain the fundamentals of probability metrics, outline new approaches to portfolio optimization, and discuss a variety of essential risk measures. Using numerous examples, they illustrate a range of applications to optimal portfolio choice and risk theory, as well as applications to the area of computational finance that may be useful to financial engineers.
Keywords: Risk assessment,Portfolio management,Stochastic processes,Đánh giá rủi ro,Quản lý danh mục đầu tư,Quy trình ngẫu nhiên; Mathematical models,Mathematical models,Mô hình toán học,Mô hình toán học